Risk Factors Associated with Symptoms of Respiratory Disorders in Brick Industry Workers: Literature Review - Muhammad Fadli Ramadhansyah; Onny Setiani; Budiyono Budiyono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Making bricks is an informal home industry with a significant dust exposure risk. Numerous risk factors contribute to respiratory symptoms, including dust exposure, duration of exposure, length of work, type of job, usage of Personal Protective Equipment (PPE), and smoking behaviours. This study examined the association between dust exposure and risk variables for respiratory symptoms in employees in the brick sector. Article searches were carried out through PubMed, Scopus, ProQuest, Science Direct, Portal Garuda Indonesia, Sinta, and Google Scholar. The articles were selected with the following criteria: the dependent variable was symptoms of the respiratory disorder of brick industrial workers, the independent variable was the exposure to dust, open access to full text, and the articles selected with a publication date around 2011-2021. Based on 272 relevant articles, 21 main articles fulfil the criteria. The risk factors indicated above are associated with increased respiratory symptoms, such as reduced vital lung capacity, coughing, shortness of breath, asthma, bronchitis, headaches, and body pains. Recommendations that can be given include adopting a healthy lifestyle that includes regular exercise, appropriate relaxation, abstinence from tobacco, frequent health checkups, and personal protective equipment such as masks.